Investigation on the use bottom ash as additive in optimizing cost of road pavement structure - Mohd Amirul Hakim, Sidek (2010)
The main objective of this study is to find the relationship between the thickness of pavement with the percentage of bottom ash. The California Bearing Ratio (CBR) values are tested by adding 4% and 8% of bottom ash in pavement design as to determine thickness of the pavement using original sample and different percentage of additive. As the thickness of the pavement varies, the cost constructing the road pavement structure has been calculated for original, 4% and 8% of bottomash. The CBR value of the sample increases from 4.40% to 8.71 % as the percentage of bottom ash is increased by 4%. The addition of the original sample with 8% of bottom ash has increased the CBR value to 13.31. Overall, the addition of bottom ash to the original sample has increased the value of CBR thus decreasing the cost of constructing the road pavement structrure.